Examining the role of Web site information in facilitating different citizen-government relationships: A case study of state Chronic Wasting Disease Web sites - Eschenfelder, Kristin R. (My University, 2007)
This paper develops a framework to assess the text-based public information provided on program level government agency Web sites. The framework informs the larger e-government question of how, or whether, state administrative agencies are using Web sites in a transformative capacity?to change relationships between citizens and government. It focuses on assessing the degree to which text information provided on government Web sites could facilitate various relationships between government agencies and citizens. The framework incorporates four views of government information obligations stemming from different assumptions about citizen?government relationships in a democracy: the private citizen view, the attentive citizen view, the deliberative citizen view, and the citizen?publisher view. Each view suggests inclusion of different types of information on government agency web sites. The framework is employed to assess state Web sites containing information about chronic wasting disease, a disease effecting deer and elk in numerous U.S. states and Canada.
Keywords: chronic wasting disease; government information; government website